PENGARUH KONTROL DIRI TERHADAP MOBILE LEGENDS ADDICTION PADA SISWA SMP NEGERI 22 KOTA JAMBI - Artita, Exsa; Rasimin, Rasimin; Ferdiansyah, Muhammad (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This mobile legends game is usually played by anyone from children to the elderly. This phenomenon can be seen from the large number of children who play Mobile Legends in every game center, both in cities and villages. This research aims to find out how much self-control students have when they are addicted to mobile legends, to find out the level of mobile legends addiction in students and to find out whether there is a significant influence between self-control and addiction to mobile legends. for students in class VII and VIII of SMP Negeri 22 Jambi City. Data collected from 69 respondents was determined using a purposive sampling technique. The data was processed using percentage techniques and simple regression analysis. Research conducted by researchers using ex post facto methods is classified as quantitative research. This research uses instruments, processing data with numbers. The results of the research show that the level of self-control of students at SMP Negeri 22 Jambi City is in the high category with a percentage of 66.92%. The level of mobile legends addiction among students at SMP Negeri 22 Jambi City is in the high category with a percentage of 62.55%. The research results of the R square table show that the value obtained is 0.051, which means that the Self Control variable (X) contributes to Mobile Legends Addiction (Y) in students by 5.1% with the interpretation "Low but certain". with a calculation of (0.051 x 100%) apart from that being influenced by other variables not studied. The regression model obtained shows that if self-control (X) increases by 1 unit it will reduce mobile legends addiction (Y) in students by 0.331. This means that the greater the student's self-control, the less addictive the student will be to Mobile Legends.